1999
DOI: 10.1152/ajpendo.1999.277.6.e1046
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 stimulates heat shock protein 27 induction in osteoblasts: involvement of p38 MAP kinase

Abstract: We previously reported that endothelin-1 (ET-1) activates p42/p44 mitogen-activated protein (MAP) kinase in osteoblast-like MC3T3-E1 cells and consequently induces synthesis of interleukin-6. In the present study, we investigated the effect of ET-1 on the induction of heat shock protein 27 (HSP 27) in MC3T3-E1 cells. ET-1 time and dose dependently stimulated HSP 27 accumulation. ET-1 induced an increase in the levels of mRNA for HSP 27. Both staurosporine and calphostin C, inhibitors of protein kinase C (PKC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 35 publications
4
46
2
Order By: Relevance
“…The maximum effect of SP600125 on HSP27 accumulation was observed at 10 mmol/l, which caused about an 80% reduction in the ET-1 effect. We previously reported that ET-1 increased the levels of HSP27 with a Western blot analysis using the antibodies for HSP27 utilized in the immunoassay (14). We confirmed that the ET-1-increased HSP27 levels were similarly detectable using the commercially obtained antibodies for HSP27 (Fig.…”
Section: Effect Of Sp600125 On Et-1-stimulated Hsp27 Accumulation In supporting
confidence: 83%
See 4 more Smart Citations
“…The maximum effect of SP600125 on HSP27 accumulation was observed at 10 mmol/l, which caused about an 80% reduction in the ET-1 effect. We previously reported that ET-1 increased the levels of HSP27 with a Western blot analysis using the antibodies for HSP27 utilized in the immunoassay (14). We confirmed that the ET-1-increased HSP27 levels were similarly detectable using the commercially obtained antibodies for HSP27 (Fig.…”
Section: Effect Of Sp600125 On Et-1-stimulated Hsp27 Accumulation In supporting
confidence: 83%
“…It is recognized that HSP27 phosphorylation is catalyzed by the MAP kinases such as p38 MAP kinase (1). We previously reported that the phosphorylation of p38 MAP kinase induced by ET-1 occurs within 10 min and returns to the basal level until 60 min after the ET-1 stimulation, suggesting that the ET-1-activated p38 MAP kinase affects their substrates within 1 h (14). On the other hand, the levels of HSP27 in unstimulated MC3T3-E1 cells were quite low (, 1 ng/mg.protein) (14).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations